Técnicas de mensuração para sondagem gástrica em recém nascidos: uma revisão de literatura - Silva, Paloma Nobre Justino da [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Objective: To identify, in the literature, evidence on techniques for measuring the gastric tube in newborns. Methods: This is an integrative literature review, which helps to synthesize the results of previous research on the subject, for its use in practice.The sample selection was performed by accessing the databases, via the Regional Portal of the Virtual Health Library (VHL), where articles were obtained in the following databases: LILACS, IBECS, Medline, BDENF-ENF. The following databases were also accessed: CINAHL, Web of Science, Scopus and Pubmed. Results: A total of 398 articles were found, and 7 were selected. There was a predominance of international and English-language articles. Studies that compared the main measurement techniques found in the literature and the evaluation of the main techniques developed by nursing predominated. Conclusion: Four techniques emerged in the study for measuring the probe to be introduced in the newborn, NEX, NEMU, formula with the use of weight and formula with the use of height, the formula with weight was cited as a measure commonly used in neonatology and proving to be safer

Objetivo: Identificar, na literatura, evidências sobre as técnicas de mensuração da sonda gástrica em recém-nascidos. Método: Trata-se de uma revisão integrativa da literatura, a qual auxilia para a síntese dos resultados de pesquisas anteriores sobre o assunto, para sua utilização na prática. Realizada a estratégia de busca nas bases de dados no mês de setembro de 2021, sem limitação de ano. A seleção da amostra foi realizada pelo acesso às bases de dados, via Portal Regional da Biblioteca Virtual de Saúde (BVS), onde obteve-se artigos nas seguintes bases de dados: LILACS, IBECS, Medline, BDENF-ENF, e também nas bases, CINAHL, Web of Science, Scopus e Pubmed Resultados: Foram encontrados 398 artigos, e selecionados 7. Predominou artigos internacionais e na língua inglesa. Predominou estudos que compararam as principais técnicas de mensuração encontradas na literatura e também a avaliação das principais técnicas desenvolvidas pela enfermagem. Conclusão: Emergiu no estudo quatro técnicas para mensuração da sonda a ser introduzida no recém nascido, NEX, NEMU, fórmula com utilização de peso e fórmula com a utilização da altura, sendo a fórmula com o peso, citada como uma medida comumente utilizada em neonatologia e mostrando-se mais segura.
Measurement techniques for gastric probing in newborns: a literature review
Keywords: Enteral nutrition; Infants; Newborn; Intubation; Nutrição enteral; Recém-nascido; Intubação gastrointestinal; Gastrointestinal